HUBUNGAN PERILAKU PEMBERIAN MAKANAN DENGAN STATUS GIZI BALITA USIA 1-3 TAHUN DI POSYANDU DESA LARANGAN WILAYAH KERJA PUSKESMAS CANDI - Hotmaida Siagian; Anita Harti Febrianti (JURNAL PENELITIAN KESEHATAN, 2016)
Feeding behavior greatly influence the nutritional status of children. Provision of adequatefood quality and quantity will support the growth and development of toddlers.the problem withthis study was toddler less or poor nutritional status caused many parents still do not know howgood feeding like any attention to nutritional needs of children in those food. This study aims toidentify the relationship of feeding behavior by the nutritional status of children aged 1-3 years inthe village of Larangan IHC. The design study is a descriptive, survey research methods areanalytic, and by cross-sectional approach. The research was conducted in the village of Prohibitionand a large integrated health as much as 49 sample respondents by making simple randomsampling technique. Independent variable in this study is the feeding behavior of the dependentvariable while the nutritional status of children. The data collection is done by filling kuesioner andobservation nutritional status of children through the KMS. Results of collecting further data weretabulated and using the Fisher test to determine the relationship of independent variables with thedependent variable, with significance level α = 0.05. The results obtained using Fisher's test resultswith a significant level of p = 0.000 indicating that feeding behavior associated with nutritionalstatus of children. Based on data analysis can be concluded that the feeding behavior associatedwith nutritional status of children aged 1-3 years